2018
DOI: 10.1080/15592294.2018.1549769
|View full text |Cite
|
Sign up to set email alerts
|

Genome-epigenome interactions associated with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome

Abstract: Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a complex disease of unknown etiology. Multiple studies point to disruptions in immune functioning in ME/CFS patients as well as specific genetic polymorphisms and alterations of the DNA methylome in lymphocytes. However, potential interactions between DNA methylation and genetic background in relation to ME/CFS have not been examined. In this study we explored this association by characterizing the epigenetic (~480 thousand CpG loci) and genetic (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(69 citation statements)
references
References 77 publications
(101 reference statements)
1
68
0
Order By: Relevance
“…In line with this theory, it should be noted that during the preparation of the current manuscript, McGowan's group published the results of a methylation genome-wide study including a screening of~4.3 million single nucleotide polymorphisms in 61 patients with ME/CFS and 48 matched healthy control subjects; they found significant genome-epigenome interactions associated with, and possibly involved in, the mechanisms of this disease. 71 This finding further supports the idea that genome-wide methylation studies must be analyzed in the context of genomic individual polymorphisms.…”
Section: April 2019supporting
confidence: 66%
See 1 more Smart Citation
“…In line with this theory, it should be noted that during the preparation of the current manuscript, McGowan's group published the results of a methylation genome-wide study including a screening of~4.3 million single nucleotide polymorphisms in 61 patients with ME/CFS and 48 matched healthy control subjects; they found significant genome-epigenome interactions associated with, and possibly involved in, the mechanisms of this disease. 71 This finding further supports the idea that genome-wide methylation studies must be analyzed in the context of genomic individual polymorphisms.…”
Section: April 2019supporting
confidence: 66%
“…Although a paucity of studies aiming at evaluation of the ME/CFS epigenome was found, a total of 230 CFS and 115 healthy control subject samples have already been assayed by genome-wide DNA methylation approaches, upon including the recent study by the McGowan's group 71 ; and a total of 127 CFS and 128 healthy control subjects have been tested for ncRNA DE by multiplex assays. Heterogeneity of studies, however, limits study value for stratified TE screenings, calling for further efforts.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of methyl groups at promoters may contribute to a hypometabolic state by down-regulating the expression of genes involved in key metabolic pathways. The ME/CFS phenotype is linked to differential methylation in genes associated with immune function and cellular metabolism [48,65,66]. For example, a 2017 study [48] detected 12,608 differentially methylated sites predominantly at cellular metabolism genes, changes that also could be related to patient quality of life health scores.…”
Section: Global Research Into Me/cfs Biologymentioning
confidence: 99%
“…169 Specific DNA methylation patterns have been detected in response to the external and internal environment (e.g., stress). [170][171][172] DNA methylation patterns change with age, smoking, and disease states, including in hypoxic conditions. [173][174][175] The silent hypoxemia observed with some COVID-19 patients may lead to alterations in DNA methylation patterns.…”
Section: Epigenetic Basicsmentioning
confidence: 99%
“…Specific DNA methylation patterns have been detected in response to the external and internal environment (e.g., stress). [170][171][172] In response to trauma and chronic stress, there are epigenetic changes in DNA methylation that alter gene expression and modulate the stress response. Post-traumatic stress disorder (PTSD) is a mental disorder that develops after a person is exposed to a traumatic event such as sexual assault, bank robbery, warfare, and abuse.…”
Section: Stress and Epigeneticsmentioning
confidence: 99%